"Ex vivo" and "in silico" study of human common carotid arteries pressure response in physiological and inverted state - Cieślicki, Krzysztof; Piechna, Adam; Lombarski, Leszek; Ciszek, Bogdan (Zielona Góra: Uniwersytet Zielonogórski)
Arterial walls are a multilayer structures with nonlinear material characteristics. Furthermore, residual stresses exist in unloaded state (zero-pressure condition) and they affect arterial behavior. To investigate these phenomena a number of theoretical and numerical studies were performed, however no experimental validation was proposed and realized yet. We cannot get rid of residual stresses without damaging the arterial segment. In this paper we propose a novel experiment to validate a numerical model of artery with residual stresses.
Keywords: artery mechanics; residual stresses; pressure-inflation test; common carotid artery